Observing Beyond the Eyes: A Rare Case Report of Pigmentary Retinopathy. - Nguyen, Kimberley; Vricella, Marilyn; Mozlin, Rochelle (Optometry & Visual Performance, 2021)
Background: This case highlights how a patient's physical extra-ocular features and behavioral characteristics guided an eye exam, where the finding of atypical retinitis pigmentosa (RP) led to the final diagnosis of Bardet-Biedl Syndrome (BBS). BBS is a serious multisystem condition consisting of atypical RP, polydactyly, central obesity, developmental delays, hypogonadism, and renal dysfunction. Case Report: A thirteen-year-old Hispanic female was seen at the University Eye Center due to longstanding decreased vision, which had not improved with the use of spectacles. The patient had a history of developmental delays, central obesity, and nyctalopia. Upon observation, a history of polydactyly was noted, leading to the suspicion of BBS and possible correlated retinal changes. This finding prompted further investigation, and the patient was diagnosed with atypical RP associated with BBS. Further management involved referrals for low vision and social services. Conclusion: The diagnosis and management for this patient relied heavily on close observation of her physical features. BBS is not always diagnosed at birth, unless polydactyly is present. Otherwise, the condition may be diagnosed when systemic manifestations have become more advanced. A more timely diagnosis allows proper treatment and management to prevent life-threatening